2004
DOI: 10.1103/physrevlett.93.056401
|View full text |Cite
|
Sign up to set email alerts
|

Giant Electron-Electron Scattering in the Fermi-Liquid State ofNa0.7CoO2

Abstract: The in-plane resistivity rho and thermal conductivity kappa of single crystal Na0.7CoO2 were measured down to 40 mK. Verification of the Wiedemann-Franz law, kappa/T=L(0)/rho as T-->0, and observation of a T2 dependence of rho at low temperature establish the existence of a well-defined Fermi-liquid state. The measured value of coefficient A reveals enormous electron-electron scattering, characterized by the largest Kadowaki-Woods ratio A/gamma(2) encountered in any material. The rapid suppression of A with ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 29 publications
8
86
0
Order By: Relevance
“…In Fig. 4, it is also shown that the ͑T͒ data of LNO-MW thin film, in the same temperature range, devi- ates from the T 3/2 behavior and seems to obey the expression 35, the ratio r KW close to a 0 indicates strong electron correlations, further suggesting that such electron-electron scattering can be related to the proximity of a nearby Mott transition.…”
Section: 28mentioning
confidence: 83%
“…In Fig. 4, it is also shown that the ͑T͒ data of LNO-MW thin film, in the same temperature range, devi- ates from the T 3/2 behavior and seems to obey the expression 35, the ratio r KW close to a 0 indicates strong electron correlations, further suggesting that such electron-electron scattering can be related to the proximity of a nearby Mott transition.…”
Section: 28mentioning
confidence: 83%
“…Such behavior is similar to that observed in Na 0.7 CoO 2 . [4] However, out-of-plane resistivity shows a weak semiconducting behavior below 12 K. Figure 2d indicates that the weak semiconducting behavior obeys thermal activation behavior with an activation energy of 0.013 meV. At high temperature, the out-of-plane resistivity shows metallic behavior up to room temperature.…”
Section: Methodsmentioning
confidence: 97%
“…This suggests that the electronic correlation in K 0.49 RhO 2 is weaker than that in Na x CoO 2 , although the T 2 law indicates significant correlation. Indeed, ρ of Na x CoO 2 is proportional to T 2 under the magnetic field [28], and we expect that the spin fluctuations are weaker in K 0.49 RhO 2 than in Na x CoO 2 , because the magnetic field suppresses the spin fluctuations.…”
Section: Methodsmentioning
confidence: 99%